2009
DOI: 10.2141/jpsa.46.95
|View full text |Cite
|
Sign up to set email alerts
|

Expression Pattern of WWP1 in Muscular Dystrophic and Normal Chickens

Abstract: The WW domain containing E ubiquitin protein ligase (WWP ) is classified into one of ubiquitin ligases which play an important role in ubiquitin-proteasome pathway. Previously, we identified the gene as a candidate gene of chicken muscular dystrophy by linkage analysis and sequence comparison. However, the mechanism causing pathological changes and underlaying gene function remains elucidated. In the present study, we analyzed the gene expression in various muscles and tissues of normal chickens, and compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Moreover, the expression was altered in liver and kidney, unaffected tissues. The result suggested that WWP1 expression level lowered in dystrophic phenotype is not directly related to the cause of disease in chicken muscular dystrophy, whereas mutated WWP1 does not function properly to cause the onset of chicken muscular dystrophy (Matsumoto et al, 2009).…”
Section: Genetical Analysis For Chicken Muscular Dystrophymentioning
confidence: 95%
“…Moreover, the expression was altered in liver and kidney, unaffected tissues. The result suggested that WWP1 expression level lowered in dystrophic phenotype is not directly related to the cause of disease in chicken muscular dystrophy, whereas mutated WWP1 does not function properly to cause the onset of chicken muscular dystrophy (Matsumoto et al, 2009).…”
Section: Genetical Analysis For Chicken Muscular Dystrophymentioning
confidence: 95%
“…Moreover, it is implicated in several diseases, such as cancers, infectious diseases, neurological diseases and aging. Northern blot analysis shows a high expression of transcripts in skeletal and cardiac muscles [ 61 ]. Full-length of chicken WWP1 shares 83% amino acid identity with human WWP1 protein [ 62 ].…”
Section: Genetic Linkage Analysis Of Am Genementioning
confidence: 99%
“…The WWP1 is the most prominent among the family members tested. They are characterized by a similar domain structure with an N-terminal, membrane interacting C2 domain, 2–4 WW domains (three domains in the case of chickens) and a C-terminal HECT domain [ 61 ] (see Figure 5 a). Despite intensive studies on oncogenic characters, the role of WWP1 to muscular functions has not yet been fully understood.…”
Section: Wwp1: E3 Ubiquitin Ligasesmentioning
confidence: 99%